(untitled) (Ghana Journal of Science, Technology and Development, 2022)
This study assessed nutrition knowledge, cooking practices, and consumption of indigenous leafy vegetables (IGLVs) among households in the Sagnarigu Municipality, Ghana. A structured questionnaire was employed to collect data on socio-demographics, nutrition knowledge scores, cooking practices, and consumption of IGLVs in the Sagnarigu Municipality. The study was cross-sectional, with a multi-stage sampling to select 399 respondents responsible for preparing family meals. More than half of the respondents had a low nutrition knowledge of IGLVs. Respondents with basic education were 67% (OR = 0.410, 95% CI: 0.170–0.986, p = 0.047) less likely to have high nutrition knowledge of IGLVs than those with tertiary education. Most respondents (65.7%) chopped their IGLVs before washing, and almost all (90.2%) discarded stock after cooking. Concerning the consumption of IGLVs, almost all respondents’ households consumed kenaf and jute leaves representing 90.2% and 99.5% respectively. A few of the respondents indicated that availability, low cost and high nutrient content were significant drivers in the consumption of IGLVs (27.1%, 13.3% and 8.8%, respectively). Therefore, interventions by both the government and non-governmental organisations to increase nutrition knowledge and consumption of IGLVs should include strategies to promote the production, utilisation, and commercialisation of IGLVs, especially in the Northern Region.